Preconceito racial no discurso do humor: um viés de construção da identidade negra - Freitas, Patricia Helena de (2007)
The present research intended to investigate how the racist discourse (re)produces itself in jokes that circutate(d) in Brazil, taking the black people as theme. On the contrary of what normally is believed, jokes do not constitute in innocent humor texts. The jokes that point the black people enhance the difference among ethnic groups and not the democratic equality. They spread the racist discourse that finds support in the ideology of the white people culture, that tries to interrupt the black people access to education, to the work market and to worthy life conditions. During the path traced to the development of this work, we tried to demonstrate, based on the theoretical assumptions of French Discourse Analysis, how the humoristic discourses, socio-historically built from of a discursive memory, can link socially established prejudices. The basic corpus that served as the work field is made of a selection of jokes collected from humor books and Internet sites. For the intended analysis, typical semantic and discursive aspects of the jokes that are being studied were considered. The repetition of the saying in racist jokes made it possible the organization of the corpus in paraphrastic families whose base utterances consolidate the racist discourse.